2012
DOI: 10.1097/ftd.0b013e3182731809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tacrolimus Intraindividual Variability and CYP3A5 Genetic Polymorphism on Acute Rejection in Kidney Transplantation

Abstract: The IIV of tacrolimus trough concentrations had a significant impact on rejection-free survival. The effect was influenced by CYP3A5 polymorphism, although the tacrolimus variability itself was not determined by the CYP3A5 polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 24 publications
11
108
4
2
Order By: Relevance
“…A high intraindividual pharmacokinetic variability of tacrolimus has been associated with a poor long-term transplant outcome (17,25). This study shows that IIV of dosenormalized C min in pediatric patients is significantly higher for Tac-OD compared with Tac-BID (21.4 AE 7.6% vs. 16.5 AE 10.2%, p ¼ 0.033).…”
Section: Once-daily Tacrolimus In Pediatric Patientsmentioning
confidence: 56%
See 1 more Smart Citation
“…A high intraindividual pharmacokinetic variability of tacrolimus has been associated with a poor long-term transplant outcome (17,25). This study shows that IIV of dosenormalized C min in pediatric patients is significantly higher for Tac-OD compared with Tac-BID (21.4 AE 7.6% vs. 16.5 AE 10.2%, p ¼ 0.033).…”
Section: Once-daily Tacrolimus In Pediatric Patientsmentioning
confidence: 56%
“…Intra-individual variability (IIV) of tacrolimus levels was also compared (17). For calculation and comparison of IIV between two formulations, the results of the tacrolimus-level measurement between 6 months prior to drug switching and 6 months after drug switching were included.…”
Section: End Pointsmentioning
confidence: 99%
“…There are several other studies also demonstrating that high tacrolimus variability, measured either by standard deviation or %CV, increases the risk of acute rejection and poor graft outcomes. 9, 11, 13 However, none of these studies assessed the impact of tacrolimus variability on racial disparities. Thus, the results of our investigation are confirmatory with regards to the impact of tacrolimus variability on posttransplant outcomes in the overall population and are novel with regards to its impact on disparities for AAs.…”
Section: Discussionmentioning
confidence: 99%
“…8, 27 The impact of CYP 3A5 on tacrolimus variability is not fully elucidated, with both positive and negative associations in the literature. 11, 3335 However, given the limitations of these studies, including small sample-size and limited information on race, the true impact of CYP 3A5 polymorphisms of tacrolimus trough variability has yet to be determined. 13 It is important to note that we did not assess the correlation between CYP 3A5 genotype, tacrolimus variability and outcomes in this study; thus, future studies assessing genotype and its impact on tacrolimus variability and clinical outcomes, particularly within AA recipients, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence for the clinical importance of Tac IPV was obtained by Borra et al who found that the within-patient variability in Tac is a significant risk factor for reaching a composite end point consisting of graft loss, biopsyproven chronic allograft nephropathy and 'doubling in plasma creatinine concentration in the period between 12 months posttransplantation and last follow up [48]. A high Tac IPV was also associated with more acute rejection after kidney transplantation [49]. Recently, Sapir-Pichhadze et al observed that a higher Tac IPV was associated with more late allograft rejection, transplant glomerulopathy, graft loss, and death with a functioning transplant [50].…”
Section: Intrapatient Variabilitymentioning
confidence: 98%